2020
DOI: 10.1021/acs.macromol.9b01551
|View full text |Cite
|
Sign up to set email alerts
|

Optical Alignment of Si-Containing Nanodomains Formed by Photoresponsive Amorphous Block Copolymer Thin Films

Abstract: A series of amorphous block copolymers (BCPs), consisting of a low glass transition polydimethylsiloxane (PDMS) block associated with a photo-responsive azobenzene-containing poly(disperse red 1 methacrylate-co-alkyl methacrylate) (P(DR1MA-co-RMA)) block, was prepared from a PDMS macro-chain transfer agent used for the reversible addition−fragmentation chain-transfer (RAFT) copolymerization of binary mixtures of methacrylate monomers of various compositions. The resulting BCPs containing up to 40 wt. % of azo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Fleury et al developed a new approach to prepare well-defined poly(dimethyl siloxane) (PDMS)-based AZ-containing LCBCs. 110 By changing the volume fraction of the AZ-containing block, multifarious self-assembled nanostructures were observed in the thin film, while surface-relief grating (SRG) inscription into these LCBC layers led to a typical sinusoidal surface modulation. Subsequently, combining the SRG photo-inscription with the MPS of the AZ-containing LCBC via solvent vapor annealing, laterally ordered in-plane PDMS nanocylinders over a large area were formed, as shown in Fig.…”
Section: Pdsa Of Lcbcsmentioning
confidence: 99%
“…Fleury et al developed a new approach to prepare well-defined poly(dimethyl siloxane) (PDMS)-based AZ-containing LCBCs. 110 By changing the volume fraction of the AZ-containing block, multifarious self-assembled nanostructures were observed in the thin film, while surface-relief grating (SRG) inscription into these LCBC layers led to a typical sinusoidal surface modulation. Subsequently, combining the SRG photo-inscription with the MPS of the AZ-containing LCBC via solvent vapor annealing, laterally ordered in-plane PDMS nanocylinders over a large area were formed, as shown in Fig.…”
Section: Pdsa Of Lcbcsmentioning
confidence: 99%
“…The responsivity of LC BCPs has considerable potential for user-defined and well-controlled programmable nanopatterning. Optical alignment of LC BCPs using the Weigert effect in Azo-based mesophases has been proven particularly effective because of the noncontact nature of the stimulus and the ease with which optical illumination of samples can be controlled. ,, Azo mesogens align orthogonal to the electric-field vector E of linearly polarized actinic light due to repetitive trans–cis–trans photoisomerization cycles under persistent illumination. One of the earliest reports regarding the optical alignment of LC BCPs is by Ikeda et al They reported that PEO-based Azo-containing LC BCPs naturally form perpendicularly oriented cylinders in thin films; however, the LC BCPs were reoriented to in-plane parallel cylinders upon irradiation by linearly polarized light (Figure a,b).…”
Section: Nanopatterning With Lc Block Copolymers and Oligomersmentioning
confidence: 99%
“…The use of light to guide the orientation of azobenzene-containing microdomains is well-established, as evidenced by the work of Ikeda, Seki, and co-workers, where a parallel alignment of cylindrical microdomains in the BCP films was realized upon exposure to polarized visible light at high temperatures above 130 °C. , A further example is where Spiridon and co-workers generated surface relief gratings by use of linearly polarized visible light to guide the orientation of cylindrical microdomains during solvent vapor annealing of the BCP film . However, the relatively high T g of the azobenzene-containing blocks, arising from a liquid crystalline (LC) alignment, makes it difficult to manipulate the self-assembly of the copolymer at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 A further example is where Spiridon and co-workers generated surface relief gratings by use of linearly polarized visible light to guide the orientation of cylindrical microdomains during solvent vapor annealing of the BCP film. 32 However, the relatively high T g of the azobenzenecontaining blocks, arising from a liquid crystalline (LC) alignment, makes it difficult to manipulate the self-assembly of the copolymer at low temperatures. Importantly, if an alkyl spacer is inserted between the main chain and the azobenzene moiety, a significant reduction in the T g of the azobenzenecontaining polymer occurs when the trans-isomer is converted into the cis-isomer, as discussed by Wu and co-workers.…”
Section: Introductionmentioning
confidence: 99%